2013
DOI: 10.2147/ppa.s50436
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 10-week core stabilization exercise training and detraining on pain-related outcomes in patients with clinical lumbar instability

Abstract: Background and aimsClinical lumbar instability causes pain and socioeconomic suffering; however, an appropriate treatment for this condition is unknown. This article examines the effect of a 10 week core stabilization exercise (CSE) program and 3 month follow-up on pain-related outcomes in patients with clinical lumbar instability.MethodsForty-two participants with clinical lumbar instability of at least 3 months in duration were randomly allocated either to 10 weekly treatments with CSE or to a conventional g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 18 publications
2
36
0
3
Order By: Relevance
“…The results of this study showed that spinal stabilization exercises had a significant effect on functional ability and chronic pain in male dentists, which is consistent with studies by Jadeian et al (2012), Puntumetakul et al (2013) and Wang et al (2012).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of this study showed that spinal stabilization exercises had a significant effect on functional ability and chronic pain in male dentists, which is consistent with studies by Jadeian et al (2012), Puntumetakul et al (2013) and Wang et al (2012).…”
Section: Discussionsupporting
confidence: 92%
“…It is recommended to use these exercises in treating patients with segmental instability of the low back (16). Puntumetakul et al studied the effects of 10 weeks of central stabilization training on back pain in patients with lumbar instability, and concluded that 10 weeks of central stability training had a long lasting effect on outcomes and improved the function of the abdominal muscles compared to conventional treatments (17). Wang et al compared general and central stability exercises and concluded that central stability exercises were more effective in reducing pain and functional improvement of chronic LBP (18).…”
Section: Introductionmentioning
confidence: 99%
“…Increase in the cross-sectional area of the lumbar multifidus as a direct result of core stability exercises can be demonstrated within 6 weeks [37]. Core stabilization exercises with the abdominal drawing in maneuver technique has been found to primarily activate the deep abdominal muscles with minimal activity of the superficial muscles [38]. Core stability exercises focus on the lumbar multifidus and transversus abdominis muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Estudos mostram que cerca de 80% da população mundial, em algum momento de suas vidas, apresentará dores e desconforto na região das costas, provavelmente, sendo a maior incidência na região lombar (PUNTUMETAKUL et al, 2013;COX, 2002). São vários os fatores que podem desencadear a incidência de dores nas costas, sobretudo na região lombar, por ser esta a região de maior desconforto em relação à manutenção de uma boa postura.…”
Section: Discussionunclassified
“…O treinamento específico da musculatura do tronco é de extrema importância para a manutenção da saúde e da qualidade de vida, seja a médio ou a longo prazo, assim como o treinamento das variáveis interdependentes que auxiliam sua função, como a relação entre as capacidades físicas, sobretudo força e resistência (PUNTUMETAKUL et al, 2013).…”
Section: Introductionunclassified